Effect of Community-Acquired Pneumonia on Acute Exacerbation of Chronic Obstructive Pulmonary Disease. (4th July 2021) - Niu, Yuanyuan; Xing, Yanli; Li, Jianfeng; Shui, Wei; Gu, Yuting; Zhang, Changran; Du, Hongchun
Abstract: Community-acquired pneumonia (CAP) is a major contributor to hospitalization for acute exacerbations of chronic obstructive pulmonary disease (AECOPD). The clinical manifestations of AECOPD with and without CAP are confusing. The difference in the survival or readmission rate of AECOPD with or without CAP remains controversial. A prospective cohort study was conducted to evaluate the clinical and laboratory characteristics and in-hospital outcomes of patients who were consecutively hospitalized due to AECOPD from May 2015 to December 2019. Grouping was based on chest computed tomography findings. Multivariable logistic regression was used to explore the predictors for early identification between CAP exacerbations and non-CAP exacerbations. Kaplan–Meier analysis was used to compare the cumulative survival rate and readmission rate for a 12-month follow-up between the two groups. A total of 378 patients with AECOPD were enrolled, including 200 patients with CAP and 178 patients without CAP. The presence of pleuritic pain, usage of ICS, and elevated levels of C-reactive protein and procalcitonin on admission were the predictors for the early discrimination between AECOPD with and without CAP. During a 1-year follow-up, the cumulative survival rate was lower in patients with AECOPD with CAP than in those with AECOPD without CAP (13.0% vs. 3.37%; HR: 4.099; 95% CI, 2.049–8.199; p  < 0.001), but the readmission rate was similar in both groups. Patients with first-time exacerbation due to CAP were more likely to experience subsequent pneumonic exacerbation. CAP is frequent among patients hospitalized for AECOPD and associated with increased mortality and successive pneumonic exacerbation.